Elicita????o de requisitos auxiliada por ontologias de dom??nio - Motta, Rafael Wobeto (2016)
The Requirements Elicitation is a process dedicated to understanding the needs of customers and users, and transform these needs into system development projects. To capture such needs the requirements engineer needs to interact with business people and the most diverse areas. This interaction requires intense communication, and is greatly affected by differences in vocabulary and interpretation that exists between the business team and the team of system developers. However, the use of Architecture Information methods and ontologies bring new alternatives to treat such problems. The Architecture Information method MAIA appears to be adherent to the Requirements Elicitation, providing new insight into the process. Therefore, studies have been identified which address the use ontologies and MAIA method that can be used to support the requirements specification. The main objective of this study is to propose the requirements elicitation in cycles (REC) model, creating a new approach to the system specification, which ensures a complete, consistent and unambiguous requirements document, and which allows automated content support. This approach is based on a set of best practices aimed at improving support for communication between teams and consequently the requirements survey process as a whole.